Epidemiology, management, and prognosis of malignant large bowel polyps within a defined population. Issue 2 (February 1992) - Chantereau, M J; Faivre, J; Boutron, M C; Piard, F; Arveux, P; Bedenne, L; Hillon, P
Abstract : The population based registry of digestive tract tumours established for the department of Côte d'Or, France (population 480, 000) was used to study the epidemiology and management of malignant large bowel polyps. In a 10 year period (1976-85), 146 cases were recorded in the area. Age standardised incidence rates were 2.7 per 100, 000 for men and 1.4 per 100, 000 for women. Although incidence rates increased significantly during the study period, large bowel cancer diagnosed as a malignant polyp remained relatively rare (6.2% of all registered large bowel cancers). Two malignant polyps (1.4%) were less than 1 cm in diameter, 34 (23.3%) were more than 30 mm. Sixty patients were treated by endoscopic polypectomy, four by contact radiotherapy, 21 by surgical local excision, 58 by colectomy (10 preceded by polypectomy), and three by colotomy. Operative mortality was 8.2% after intra-abdominal surgery, 4.8% after local surgical excision, and 0% after polypectomy (p less than 0.05). All deaths occurred in patients over 65 years. The five year cumulative recurrence rates were 8.9% after surgical excision and 11.3% after endoscopic polypectomy (NS). The corresponding five year net survival rates were 86.1% and 95.9%. Endoscopic excision alone can be considered a sufficient treatment for adenomas with malignant change unless there is evidence of incomplete resection or a high risk of lymph node metastases.